What is the level of nutrition literacy of Saudi adolescents? A national wide exploratory cross-sectional study - Bookari, Khlood (Frontiers in Nutrition, 2023)
Background: Despite being a prolific research topic, studies evaluating nutrition literacy in the Arab world are scant and still nonexistent in the Kingdom of Saudi Arabia. Therefore, a national study was launched with the aim to (1) assess nutrition literacy among Saudi adolescents aged 10-19 years old and (2) determine its correlates. Methods: A cross-sectional study was launched across all Saudi provinces between 29 April and 6 June 2022, enrolling a convenience sample of 2115 adolescents (mean age= 16.8 ± 2.5; girls: 48.7%). An online self-administered questionnaire was disseminated to eligible participants to collect relevant data. Results: Study findings showed that nearly half of the adolescents (44.6%) had poor nutrition literacy. The male gender doubled the risk of adolescents having poor nutrition literacy (OR=2.0, CI=1.5-2.5, p<0.001). Northern border residents were 14 times more likely to be nutritionally illiterate, in contrast to adolescents residing in Riyadh (OR=14.0, CI=7.3-28.0, p<0.001). Adolescents were more likely to be nutritionally illiterate if they were underweight or overweight (OR=2.7, CI=1.6-4.7, p<0.001; OR=2.2, CI=1.7-2.9, p<0.001). School students had 2 times more risk of having poor nutrition literacy, in contrast to those who were enrolled in universities (OR=1.8, CI=1.4-2.4, p<0.001). Nutrition illiteracy was 4 times higher among adolescents having caregivers else than their parents (OR=3.9, CI=2.2-6.9, p<0.001). Parental education level also contributed to determining adolescents’ nutrition literacy status. Conclusions: It has become essential to courage the development of supportive school environments in Saudi Arabia to promote nutrition education and improve adolescents’ nutrition literacy. Without a doubt, this calls for taking a holistic approach on the part of education and health ministries, nutrition professionals, educators, parents, and, most importantly, the teenagers themselves, who must have the desire and motivation to learn.